Factors Affecting the Level of Disclosure of Human Resources for Saudi Listed Companies - Alharbi, Nawal (Archives of Business Research, 2022)
Abstract Human resources (HR) information is a critical tool for assessing the effectiveness of HR management and encouraging competitive advantage between companies. Disclosing this information is especially useful for prospective employees, where they are informed on the HR services available within companies. The study aims to examine the factors affecting the level of Human Resources Disclosure (HRD) in the annual reports of listed Saudi companies. Factors are classified into factors related to governance mechanisms are the size of the board of directors, the independence of board members, the number of board meetings, and the type of auditor. Factors associated with the company characteristics are profitability, leverage, liquidity, the company’s age, the size of the firm, and industry type. The final study sample consists of 363 observations of 121 Saudi non-financial companies listed on the Saudi financial market during the period from 2016 to 2018. The content analysis method was used to examine the disclosure list of 19 elements of human resources, which was developed based on previous studies. EViews software was used to analyze panel data and use a multiple regression model to test the statistical relationship between relevant factors and human resource disclosure. The regression results indicate that the independence of the board of directors, the company’s profitability, the company’s age, and the size of the company have a significant positive effect on the level of human resources disclosure for the listed Saudi companies. Whilst the size and number of board meetings, auditor type, financial leverage, liquidity, and industry type have no impact on the level of human resource information disclosure. Keywords: Human Resources Disclosure, Financial Reporting, Governance mechanisms, Company characteristics.